Rural Nostalgias and Transnational Dreams : Identity and Modernity Among Jat Sikhs - Mooney, Nicola, 1967- (Book collections on Project MUSE., 2011)
Renowned as the predominant farmers and landlords of Punjab, and long possessed of an autocthonous agricultural identity, Jat Sikhs today often live urban and diasporic lives. Rural Nostalgias and Transnational Dreams examines the formation of Jat Sikh identity amid diverse ideals and incursions of modernity, exploring the question of what it means to be Jat Sikh in the contemporary Indian city. Nicola Mooney describes a number of Jat Sikh social practices and narratives - education, professional development and employment, the making of appropriate marriage matches, and the discourse of progress - through which contemporary notions of identity are developed. She contextualizes these elements of Jat Sikh modernity against local, regional, and national histories of cultural and political differentiation, perceptions of marginality, and the expression of increasingly exclusive notions and practices of identity. Mooney argues that class practices incorporate urban Jat Sikhs into national and transnational communities, separating them from rural Jat Sikhs and confounding caste solidarities. Nevertheless, rural attachments remain important to urban identities. This is a unique ethnography that incorporates first-hand observations and local narratives to develop insights into the traditions and social memory of Jat Sikhs, as well as on the issues of urban and transnational social transformation.